Chronic loneliness and chronic social isolation among older adults. A systematic review, meta-analysis and meta-regression - Hajek, André; Sutin, Angelina R.; Posi, Giuliana; Stephan, Yannick; Peltzer, Karl; Terracciano, Antonio; Luchetti, Martina; König, Hans-Helmut (Aging & mental health, 2025)
We performed a systematic review and meta-analysis to examine the prevalence and antecedents/consequences of chronic loneliness and social isolation (i.e. enduring or persistent experience that extends over a certain period of time) among older adults. Moreover, we conducted a meta-regression to explore sources of heterogeneity. A search was conducted in four electronic databases. We included observational studies that reported prevalence and, where available, antecedents/consequences of chronic loneliness or chronic social isolation amongst older adults. Key characteristics of the studies were extracted. Across 17 studies included in the meta-analysis, the estimated prevalence of chronic loneliness was 20.8% (95% CI: 16.1-25.5%), including 21.7% among women (95% CI: 16.1-27.4%) and 16.3% among men (95% CI: 10.6-21.9%). One study reported chronic social isolation (13.4%) and found that chronic social isolation predicted higher depression scores. Meta-regressions indicated that loneliness was less prevalent when assessed with single-item measures. Regarding antecedents/consequences, spousal loss can contribute to chronic loneliness which in turn may contribute to adverse health-related outcomes. About one in five older adults experiences chronic loneliness reflecting the need to address chronic loneliness. More longitudinal research is needed on chronic loneliness and social isolation, particularly from low and middle-income countries.